2014
DOI: 10.1016/j.bbrc.2014.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Nanog positively regulates Zfp57 expression in mouse embryonic stem cells

Abstract: a b s t r a c tTo maintain the self-renewal of embryonic stem (ES) cells, several core transcription factors, including Oct3/4, STAT3, and Nanog, regulate the expression of their target genes. Zinc finger protein 57 (Zfp57) is specifically expressed in self-renewing ES cells and its expression level is reduced upon ES cell differentiation, suggesting that expression of this transcription factor is regulated by core transcription factors. In the present study, we investigated whether Zfp57 expression is regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…These results suggest that PDGF-C is involved in anchorage-dependent growth of ES cells. ES cells can grow under anchorage-independent conditions [17,29], as expected since they can give rise to benign tumors called teratomas when injected into immunodeficient mice [30]. The PDGF-R inhibitor AG1296 suppressed anchorageindependent growth of E14 ES cells in soft agar (Fig.…”
Section: Pdgf-c Is Required For Anchorage-dependent and -Independent mentioning
confidence: 57%
“…These results suggest that PDGF-C is involved in anchorage-dependent growth of ES cells. ES cells can grow under anchorage-independent conditions [17,29], as expected since they can give rise to benign tumors called teratomas when injected into immunodeficient mice [30]. The PDGF-R inhibitor AG1296 suppressed anchorageindependent growth of E14 ES cells in soft agar (Fig.…”
Section: Pdgf-c Is Required For Anchorage-dependent and -Independent mentioning
confidence: 57%
“… 151 Indeed, Nanog may participate in the upregulation of Zfp57 as demonstrated in mESCs. 152 Moreover, ZFP57 upregulation correlated with poorer patient outcome. 151 Altogether, these observations suggest ZFP57 may play a role in the maintenance and proliferation of CSCs.…”
Section: Krab-zfp/trim28 Influence On Stem Cells and Cancer Stem Cellsmentioning
confidence: 98%
“…Zfp57 was also demonstrated to influence the anchorage-independent growth of mESCs – knock-down of Zfp57 with simultaneous Nanog overexpression resulted in a reduction in the number of cell colonies. 152 Higher expression of ZFP57 is thus associated with a greater proliferation potential of ESCs. Moreover, an increased expression of ZFP57 was also observed in grade IV compared to grade II glioblastoma.…”
Section: Krab-zfp/trim28 Influence On Stem Cells and Cancer Stem Cellsmentioning
confidence: 99%
“…A study in human cohort showed that maternal folate intake caused hypomethylation of zinc finger protein 57 (ZFP57) transcripts, a master regulator of DNA methylation [94]. In addition to DNA methylation, histone acetylation H3 and H4 were also altered by maternal folate intake and was associated with high mRNA expression in CD41 T cells [95].…”
Section: Folic Acidmentioning
confidence: 99%